Sugar-glycerol cofermentations by lactobacillus hilgardii isolated from wine - Pasteris, Sergio Enrique (2009)
Glycerol catabolism was studied in Lactobacillus hilgardii X1B from wine, growing on glycerol and limiting glucose or fructose concentrations in anaerobiosis and microaerophilia. Glycerol consumption occurred simultaneously with sugar use, and it was higher with fructose as a cofermenting sugar in microaerophilia. Enzymatic activities of the glycerol kinase and glycerol dehydratase pathways were detected in both incubation conditions. In anaerobiosis, the main products were lactate, acetate, ethanol, and the intermediary product of the glycerol dehydratase pathway, 3- hydroxypropionaldehyde. However, in microaerophilia, 1,3-propanediol was also detected. In anaerobic glucose + glycerol and fructose + glycerol cultures as in microaerophilic glucose + glycerol cultures, glycerol was degraded mainly through the reductive pathway. However, when L. hilgardii X1B was grown on fructose + glycerol cultures in microaerophilia, glycerol dissimilation occurred mainly via the glycerol kinase way. According to these results, L. hilgardii X1B can degrade glycerol by producing 3-hydroxypropionaldehyde and acetic acid, both undesirable products for wine sensorial quality. © 2009 American Chemical Society.